A Review on Cultural Design Elements for Mobile Applications User Interface - Ariffin, Shamsul Arrieya; Fathil, Nur Saadah; Yatim, Maizatul Hayati Mohamad; Samsuri, Muhammad Zulhilmi (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This study examined the existing use of cultural design elements in design guidelines for mobile applications. Cultural design elements are used to include cultural values in the development of mobile applications. A review of existing design guidelines was conducted to identify cultural design elements practicality pertaining to the mobile application. The keywords "Application", "Design Guidelines", and "User Interface" were searched on ACM Digital Library, IEEE Xplore, and Scopus between 2017 and 2021, including 2022, with 281 articles before filtering and 3 articles selected after filtering. This review shows that cultural design elements in the mobile application played an important role in getting a high usability rate for user’s use. Although it is an important element, its use is still limited usage in the development of mobile applications. As a result, future research will focus on developing guidelines for mobile applications with cultural design elements appropriate for today’s technological era in a local context.